2013
DOI: 10.1523/jneurosci.3086-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Reputational Priors Magnify Striatal Responses to Violations of Trust

Abstract: Humans learn to trust each other by evaluating the outcomes of repeated interpersonal interactions. However, available prior information on the reputation of traders may alter the way outcomes affect learning. Our functional magnetic resonance imaging study is the first to allow the direct comparison of interaction-based and prior-based learning. Twenty participants played repeated trust games with anonymous counterparts. We manipulated two experimental conditions: whether or not reputational priors were provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
115
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 47 publications
22
115
0
Order By: Relevance
“…That is, previous studies have consistently demonstrated that neural pathways underlying social reward-processing and decisionmaking engage the reward-circuit (Behrens et al, 2008;De Quervain et al, 2004;Harris & Fiske, 2010;Hare et al, 2010;Jones et al, 2001;Moll et al, 2006;Phan et al, 2010;Rilling & Sanfey, 2011;Zaki & Mitchell, 2011) and that Reinforcement Learning models can be applied to social learning Fouragnan et al, 2013;Jones et al, 2001;Lin et al, 2012;Poore et al, 2012;Xiang, Lohrenz, & Montague, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, previous studies have consistently demonstrated that neural pathways underlying social reward-processing and decisionmaking engage the reward-circuit (Behrens et al, 2008;De Quervain et al, 2004;Harris & Fiske, 2010;Hare et al, 2010;Jones et al, 2001;Moll et al, 2006;Phan et al, 2010;Rilling & Sanfey, 2011;Zaki & Mitchell, 2011) and that Reinforcement Learning models can be applied to social learning Fouragnan et al, 2013;Jones et al, 2001;Lin et al, 2012;Poore et al, 2012;Xiang, Lohrenz, & Montague, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, vmPFC and striatum also encode social value (Behrens, Hunt, Woolrich, & Rushworth, 2008;Bhanji & Delgado, 2014;De Quervain et al, 2004;Fareri, Niznikiewicz, Lee, & Delgado, 2012;Hare, Camerer, Knoepfle, O'Doherty, & Rangel, 2010;Jones et al, 2001;Moll et al, 2006;Phan, Sripada, Angstadt, & McCabe, 2010;Rilling & Sanfey, 2011;Zaki & Mitchell, 2011), such as the value of an attractive face (Aharon et al, 2001;Kampe, Frith, Dolan, & Frith, 2001;O'Doherty, Winston, et al, 2003), the value of social approval/acceptance or having a good reputation (Izuma, Saito, & Sadato, 2008;Jones et al, 2011;Lin et al, 2012), the value of cooperation (Krill & Platek, 2012;Rilling et al, 2002;Stallen & Sanfey, 2013;Watanabe et al, 2014), and the value of charitable giving (Hare et al, 2010;Moll et al, 2006). Additionally, for both social and nonsocial contexts also discrepancy between expected and outcome values (e.g., reward prediction errors; Delgado, Nystrom, Fissel, Noll, & Fiez, 2000;Fareri, Chang, & Delgado, 2012;Fouragnan et al, 2013;Harris & Fiske, 2010;Jones et al, 2001;O'Doherty, Dayan, et al, 2003;Pessiglione, Seymour, Flandin, Dolan, & Frith, 2006;Phan et al, 2010;Poore et al, 2012;Schönberg, Daw, Joel, & O'Doherty, 2007;Schültz, Dayan, & Montague, 199...…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these trust-learning effects are strongly modulated by prior expectations (as is the case for non-social reward-learning effects 51 ): unexpected reciprocity in any trial induced stronger ventral striatum activity and higher investments in subsequent encounters compared with expected reciprocity 53 , suggesting that this activity may reflect a reward prediction error similar to that observed during non-social forms of reward learning. However, striatal prediction errors and behavioural learning during the outcome of trust decisions can also be suppressed when information about the opponents' trustworthiness is presented 54 , suggesting that strong priors can overrule the importance of new information gathered during single trials.…”
Section: Learning About Othersmentioning
confidence: 99%
“…Indeed, the trustor may lose the amount of money she decides to send if the trustee defects and defection is highly desirable for the trustee since it yields him the highest outcome (Camerer and Weigelt, 1988; Fouragnan, et al, 2013). However, empirical studies have shown that trustors invest more than half of their initial endowment and trustees split the amount of money they received evenly (Camerer, 2003a; Fehr and Fischbacher, 2003; Johnson and Mislin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Social preferences, such as prosociality or betrayal aversion, imply that subjects derive extra utility/disutility from trusting/distrusting behaviors (Bohnet, et al, 2008; Bohnet and Zeckhauser, 2004; Fehr and Camerer, 2007). Finally, beliefs about others built through social priors (e.g., implicit racial attitudes, group memberships) or reputation on the basis of previous experiences (via trial-and-error learning) help people estimate the utility associated with the decision options and adjust their behavior for future interactions (Chang, et al, 2011; Fareri, et al, 2012; Fouragnan, et al, 2013; King-Casas, et al, 2005). …”
Section: Introductionmentioning
confidence: 99%